Does IoT service orchestration in public services enrich the citizens' perceived value of digital society?. Issue 1 (2nd January 2022) - Hu, Guangwei; Chohan, Sohail Raza; Liu, Jianxia
ABSTRACT: The continuous growth of digital transformation aims to leverage the changes and opportunities for IoT technologies in public sector, which has created an impact on the sustainability of digital societies. The Internet of Things (IoT) contains significant challenges such as citizens' perceived value towards intention to use in public services that could stand in a way of realizing its potential benefits. Our study aims to investigate the influencing factors of citizens' usage intention concerning IoT service orchestration in public services along with the mediation influence of perceived value. A comprehensive public IoT Perceived Value Model (IoT-PVM) was enumerated to provide success factors for IoT service orchestration. This model was analytically tested by PLS-SEM approach. The results highlighted that perceived value has a mediation effect in IoT public service intentions to use with 59% perceived variance. The success of government IoT services is best measured by the perceptions of citizens, therefore, this study contributed to identifying the factors concerning public engagement with IoT service orchestration along with describing the positive role of digital society affinity. In terms of practical significance, a use case IoT model was presented with provides an intersectional perspective of citizens concerning IoT service orchestration in public services.